A phase I / IIa trial of PXS-5505, a novel pan-lysyl oxidase inhibitor, in advanced myelofibrosis - Pankit Vachhani; Peter Tan; Anne-Marie Watson; Shang-Ju Wu; Ross Baker; Stanley Cheung; Sung-Eun Lee; Chih-Cheng Chen; Tsai-Yun Chen; Hui-Hua Hsiao; Jae Hoon Lee; Lucia Masarova; et al. (Haematologica)
Myelofibrosis (MF) is a progressive disease characterized by accumulation of extracellular matrix (ECM) in the bone marrow (BM) which impairs normal hematopoiesis. While Janus kinase (JAK) inhibitors reduce spleen volume and provide symptomatic improvement, they do not resolve BM fibrosis and may cause or exacerbate anemia and thrombocytopenia. An anti-fibrotic therapy capable of normalising BM microenvironment and function remains a significant gap in the current treatment landscape.